2021
DOI: 10.1111/1750-3841.15636
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of oil, antioxidant potential, and phenolic profile of seeds isolated from Tunisian pomegranate (Punica granatum L.) cultivars

Abstract: Pomegranate (Punica granatum L.) seeds oils (PSO) from three Tunisian varieties namely Jebali, Testouri, and Gabsi were extracted by ultrasonic‐assisted extraction and analyzed for their physicochemical properties, fatty acids (FA) profile, and sterol composition. PSO of Gabsi and Testouri showed the best quality indexes in terms of peroxide and acid values and the highest oxidative stability index was observed for PSO of Gabsi ecotype (2.534 hr). Polyphenol content of PSO of Gabsi ecotype (886.909 mg/kg) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…This difference in results may be due to changes in the genomic and in plants protein expression or even of the tested strain. These results are coherent with the study of Khemakhem et al ( 38 ). They confirmed that in pomegranate, the physicochemical characterization of three Tunisian varieties (Jebali, Testouri and Gabsi) showed enormous differences in component levels, especially the phenolic compounds.…”
Section: Discussionsupporting
confidence: 93%
“…This difference in results may be due to changes in the genomic and in plants protein expression or even of the tested strain. These results are coherent with the study of Khemakhem et al ( 38 ). They confirmed that in pomegranate, the physicochemical characterization of three Tunisian varieties (Jebali, Testouri and Gabsi) showed enormous differences in component levels, especially the phenolic compounds.…”
Section: Discussionsupporting
confidence: 93%
“…The MIC values for active pomegranate extracts ranged between 30 and >90 µg/mL. The results obtained appeared to confirm the antimicrobial potential of the P. granatum varieties 17 . The chemical composition of the fruits differs depending on the cultivar, growing region, maturity, cultivation practice, climate, and storage circumstances.…”
Section: Fig 2: Zone Of Inhibition Of the Extract Against Candida Gui...supporting
confidence: 53%
“…DISCUSSION: In this experiment, we observed good antifungal activities of fruit external peel alcoholic extract of P. granatum particularly against C. guilliermondii. Antibacterial activities of P. Granatum extract are well known against Staphylococcus aureus 12,13 , Streptococcus mutans, E. coli 13 , Pseudomonas aeruginosa 13 , Propionibacterium acnes 14 , pathogenic Clostridium, Lactobacillus, Bifidobacteria, Bacillus megaterium, Corynebacterium xerosis, Enterococcus faecalis, Micrococcus luteus [15][16][17][18] . Duraipandiyan et al experimented to determine the in-vitro antifungal efficacy of P. granatum peel extract against the oral Candida compared with clotrimazole.…”
Section: Fig 2: Zone Of Inhibition Of the Extract Against Candida Gui...mentioning
confidence: 99%
“…Punica granatum L. (pomegranate), a member of the Punicaceae family, is one of the oldest plants in the world which has commercial and cultural importance. Since it is a prominent crude ingredient for the pharmaceutical, cosmetic, beverage, and food industries, the economic value of pomegranate fruits is very high (Khemakhem et al, 2021). Pomegranate fruits are frequently preferred in people's daily diets due to its vitamin, mineral, phenols, flavonoids, and antioxidant content (Boussaa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%